Performances of Jatropha and Waste Cooking Oil Biodiesel Blends Fuel Combustion using Diesel Engine - Norwazan, A. R.; Norzaima, N.; A. Rahman, M. R.; Nasir, M. S. R. (International Journal of Integrated Engineering, 2020)
High demands on biodiesel fuel usage on diesel engine is influences the manufacturer to produce more biodiesel fuel especially by using waste products instead of plant oil. Currently, waste products are easily to recycle in many ways including fuel production in order to get better environment. In addition, biodiesel fuel consuming is claimed in HC and CO emissions reduction. It shows that biodiesel fuel combustion is promising to emit the green emissions into environment and protect our planet from global warming. Biodiesel fuel consumption also is one of an alternative to support high demand and depleting of fossil fuel. Jatropha oil and waste cooking oil biodiesel fuels were produced using a two-step of transesterification process using methanol with sulfuric acid catalyst to diminish their free fatty acid level. Then, the transesterification was continued with methanol and the catalyst of potassium hydroxide. The paper focuses on the determination of chemical properties of biodiesel blends fuel using jatropha oil and waste cooking oil biodiesel fuel in different percentages. It also presents the combustion performances and emissions of both biodiesel fuels in diesel engine.